1985
DOI: 10.1130/spe201-p39
|View full text |Cite
|
Sign up to set email alerts
|

The Catskill Delta complex and the Acadian Orogeny: A model

Abstract: The Catskill Delta complex is interpreted to be the aggregate of delta-alluvial wedges and associated facies that developed in the central Appalachians and on adjacent parts of the stable craton from the Early-Middle Devonian transition to the Middle Mississippian during the Acadian orogeny.Recent interpretations of the Acadian orogeny suggest that it probably was related to oblique convergence and transcurrent movement along a major strike-slip fault zone separating the eastern margin of the North American la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 19 publications
1
111
0
Order By: Relevance
“…Closely following the Caledonian cycle of orogeny, however, was the Early Devonian (Pragian; mid-Ulsterian) inception of convergence by one or more Avalonian terranes with the southeastern margin of Laurussia. This episode of convergence, called the Acadian Orogeny, generated some of the best-known and variously interpreted delta complexes in the Appalachian Basin (Friedman and Johnson, 1966;Woodrow and Sevon, 1985;Faill, 1985;Ettensohn, 1985a). Convergence was probably transpressional, and beginning in late Early Devonian (Pragian-Emsian; mid-Ulsterian) time, progressed southwestwardly along the southeastern margin of Laurussia (Ettensohn, 1985a(Ettensohn, , 1987, resulting in a series of thick, clastic sequences that tracked the southwesterly progress of orogeny (Ettensohn, 1985a(Ettensohn, ,b, 1987.…”
Section: Acadian Complexes (Devonian-mississippian)mentioning
confidence: 98%
See 1 more Smart Citation
“…Closely following the Caledonian cycle of orogeny, however, was the Early Devonian (Pragian; mid-Ulsterian) inception of convergence by one or more Avalonian terranes with the southeastern margin of Laurussia. This episode of convergence, called the Acadian Orogeny, generated some of the best-known and variously interpreted delta complexes in the Appalachian Basin (Friedman and Johnson, 1966;Woodrow and Sevon, 1985;Faill, 1985;Ettensohn, 1985a). Convergence was probably transpressional, and beginning in late Early Devonian (Pragian-Emsian; mid-Ulsterian) time, progressed southwestwardly along the southeastern margin of Laurussia (Ettensohn, 1985a(Ettensohn, , 1987, resulting in a series of thick, clastic sequences that tracked the southwesterly progress of orogeny (Ettensohn, 1985a(Ettensohn, ,b, 1987.…”
Section: Acadian Complexes (Devonian-mississippian)mentioning
confidence: 98%
“…The word tectophase is used here in the sense of Johnson (1971) to reflect all the events in a particular pulse or phase of orogeny, mostly concentrated at a certain time and place along an orogenic belt. Ettensohn (1985aEttensohn ( , 1987Ettensohn ( , 1994, moreover, showed that each tectophase produced a third-order sequence of sediments, including delta complexes, bound by unconformities, and that the progression of an orogeny could be tracked by mapping the distribution of the sequences, both parallel and perpendicular to the strike of the foreland basin. Despite differing ages, each of the early Appalachian sequences contains a similarly ordered succession of lithologies, suggesting that each broad lithologic type in the sequence results from a specific flexural response to various phases of deformational loading or lithospheric relaxation during a tectophase in the orogen.…”
Section: Introductionmentioning
confidence: 97%
“…1). The Geneseo Formation is the basal unit of the Upper Devonian Genesee Group, part of the Catskill Delta complex deposited during the Acadian Orogeny (Ettensohn, 1985). The Geneseo Formation is a homogeneous black shale, about 30 m thick in the study area, that crops out in an E±W-trending band across the central Appalachian Plateau of New York.…”
Section: Field Observationsmentioning
confidence: 99%
“…These promontories served to localize shortening and deformation (Figure 1-7). They went through greater compression which led to greater flexural subsidence, and formed four major depocenters (Ettensohn, 1985(Ettensohn, , 1994(Ettensohn, , 2008Ferrill and Thomas, 1988;Lash and Engelder, 2011;Lavoie, 2008).…”
Section: Marcellus Formation Appalachian Basinmentioning
confidence: 99%